Pengaruh Smartcard Cek Mual Muntah Terhadap Keseimbangan Cairan Pada Pasien Post Operative Nausea And Vomiting - Juartika, Wella; Feri, Jhon; Diastuti, Agustin (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: Ostoperative Nausea and Vomiting (PONV) often leads to fluid imbalance, which affects patient recovery. This study aims to evaluate the impact of the Smart Card Cek Mual Muntah (SCMM) on maintaining fluid balance in PONV patients. Methods: The study used a descriptive design involving postoperative patients experiencing PONV. Data collection included SCMM-based symptom monitoring and fluid balance measurements (intake-output). Interventions such as antiemetic administration and IV fluids were analyzed. Results: CMM enhanced early symptom detection, timely interventions, and reduced complications related to fluid imbalance. The implementation resulted in better hydration levels and reduced PONV severity in patients. Conclusion: CMM contributes significantly to maintaining fluid balance, optimizing recovery, and reducing the risk of complications in PONV patients.